Levels of nasal exhaled hydrogen sulfide in the general population and allergic rhinitis patients. Issue 3 (7th December 2020) - Li, Lisha; Liu, Yonglin; Wang, Qiang; Wang, Zixi; Cui, Le; Xu, Yingyang; Guan, Kai
Abstract: Background: Objective measures used for the differential diagnosis and severity assessment of allergic rhinitis (AR) are still lacking. The involvement of hydrogen sulfide (H2 S) in the development of AR indicates that nasal exhaled H2 S (NeH2 S) has potential as a biomarker to be used in AR patients. This study aimed to evaluate the application value of NeH2 S measurement in the diagnosis and assessment of AR. Methods: This study was a multi‐center cross‐sectional survey conducted in Northwestern China. Demographic information collection and rhinitis assessment were completed through questionnaires. The level of NeH2 S and serum immunoglobulin E were measured. Results: The level of NeH2 S in general population ranged from 0 to 35 ppb, with a median value of 2 ppb. The NeH2 S levels in seasonal allergic rhinitis (SAR) patients were significantly lower than those in general population (2 [1, 2.75] vs. 2 [2, 3] ppb; p  = .023), and the NeH2 S value of the SAR group tended to be lower than that of the non‐allergic rhinitis (NAR) group (2 [1, 2.75] vs. 2 [2, 3] ppb; p  = .094). The subgroup of AR patients with symptoms lasting longer than 2 weeks per month had a lower NeH2 S level compared with the subgroup of patients with symptoms lasting less than 2 weeks per month (2 [1, 2] vs. 2 [2, 3] ppb; p  = .015). Conclusion: This study described the distribution range of NeH2 S levels in the general population. Further study with larger sample size was needed to clarify the relationship between NeH2 S level and AR. Abstract : This multi‐center cross‐sectional study surveyed the residents in Northwestern China and described for the first time the distribution range of NeH2 S levels in the general population. Our results showed that NeH2 S level of seasonal allergic rhinitis (SAR) patients was significantly lower than that of general population, and the NeH2 S level of the SAR group tended to be lower than that of the non‐allergic rhinitis (NAR) group.